2010
DOI: 10.2527/jas.2009-2026
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for parent-of-origin effects on genetic variability of beef traits1

Abstract: Imprinted genes are involved in many aspects of development in mammals, plants, and perhaps birds and may play a role in growth and carcass composition of slaughter animals. In the presence of genomic imprinting the expression and, consequently, the effect on the phenotype of maternal and paternal alleles are different. For genetic evaluation genomic imprinting can be accounted for by incorporating 2 additive genetic effects per animal; the first corresponds to a paternal and the second to a maternal expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(99 citation statements)
references
References 28 publications
6
91
2
Order By: Relevance
“…These results partially agreed with those reported by Engellandt and Tier (2002) and Neugebauer et al (2010) in Gelbvieh and Simmental cattle, respectively, although contradictory results were also available (Reinsch et al, 1999). The influence of the Y chromosome was previously highlighted by Kieffer and Cartwright (1968) and Schoeman (1989), who reported that even the morphology of this chromosome (i.e.…”
Section: Model Comparisonsupporting
confidence: 90%
See 4 more Smart Citations
“…These results partially agreed with those reported by Engellandt and Tier (2002) and Neugebauer et al (2010) in Gelbvieh and Simmental cattle, respectively, although contradictory results were also available (Reinsch et al, 1999). The influence of the Y chromosome was previously highlighted by Kieffer and Cartwright (1968) and Schoeman (1989), who reported that even the morphology of this chromosome (i.e.…”
Section: Model Comparisonsupporting
confidence: 90%
“…However, in mice, Schwenker and Maxon (1986) and Bü nger et al (1995) reported significant influences from the Y chromosome on growth, BW and testis weight. A similar scenario was found for the imprinting phenomenon in beef cattle where available -E-mail: joaquim.casellas@uab.cat results restricted to original researches conducted on German Gelbvieh (Engellandt and Tier, 2002) and Simmental cattle (Neugebauer et al, 2010); imprinting variability was revealed on several carcass traits. Furthermore, some imprinted quantitative trait loci have been detected in livestock species for growth and fatness traits (De Koning et al, 2001a and2011b).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations